Vitality of Proteinase K in rRTPCR Detection of SARS-CoV2 Bypassing RNA Extraction - Shukla, Alka; Gangwar, Mayank; Sharma, Gaurav; Prakash, Pradyot; Nath, Gopal (Frontiers in cellular and infection microbiology, 2021)
This study aimed to detect the SARS-COV2 viral component directly from inoculated VTM without RNA extraction. Inoculated VTMs of already tested 50 positive and 50 negative samples were divided into three groups. Group I was treated with Proteinase K (PK) followed by 3-step-heat treatment at different temperatures (25°C, 60°C, and 98°C) and stored at 4°C. Group II was directly subjected to 3-step-heat treatment without PK exposure and stored at 4°C. And group III was set-up as standard group; it was processed using Qiagen’s column based QIAamp Nucleic Acid kit and the obtained nucleic acids were stored at 4°C. These stored samples were used as a template to execute real-time polymerase chain reaction, and results were noted. Group I demonstrated 96% and 88% sensitivity for N and ORF1ab genes respectively, whereas group II demonstrated 78% and 60% when compared to the results of standard group III. Overall group I showed better results than group II when compared to group III. Thus, in situations where gold-standard reagents are not available, PK exposure and heat treatment can be employed to carry out molecular detection of SARS-CoV2 viral component.